Improved lenticule shape for hyperopic femtosecond lenticule extraction (ReLEx® FLEx): a pilot study. Issue 4 (May 2016) - Sekundo, Walter; Reinstein, Dan; Blum, Marcus
Abstract The aim of this study is to establish and to prove a new lenticule shape for the treatment of hyperopia using a 500 kHz femtosecond laser and the femtosecond lenticule extraction (ReLEx® FLEx) technique. Improved lenticule shapes with a large transition zone of at least 2 mm adjusted to the 5.75 mm optical zone were designed. A prospective pilot study on nine eyes of five patients who underwent an uncomplicated FLEx using VisuMax® femtosecond laser (Carl Zeiss Meditec AG) for spherical hyperopia was performed. Patients' mean age was 55.5 years, and the preoperative manifest spherical equivalent (SE) was +1.82 D (range +1.25 to +3.00 D). Because of the presbyopic age and in order to compensate for a possible regression, the treatment was aimed at low myopia (mean target SE was −0.88 D with a mean treatment refraction of +2.69 D). At the last follow-up, after 9 months, 33 % were within ±0.50 D and 78 % within ±1.00 D of intended correction. Thirty-three percent lost one line, and 11 % gained one line corrected distance visual acuity (CDVA). On average, the centre of the optical zone was 0.34 ± 0.17 mm from the corneal vertex. No adverse effects were observed. This pilot study confirms that the improved lenticule's design with a large optical and transition zone can achieve good centration and acceptable results for spherical hyperopia using FLEx. The next steps are to extend the study to spherocylindrical hyperopic treatments and to increase the number of eyes for better assessment of refractive outcome.